Supporting Memory for Spatial Location while Reading from Small Displays - O'Hara, Kenton; Sellen, Abigail; Bentley, Richard (Proceedings of CHI 99, 15-20 MAY 1999, 1999)
Research has shown that when people read paper documents, they develop an incidental memory for the location of information within those documents. However, this kind of spatial memory is undermined in conventional on-line scrolling interfaces. We report on an experiment in which we show that careful design of the interface can reinstate memory for spatial location. As we will show, this has particular implications for the design of interfaces for small screen displays.